FACTORS AFFECTING FROZEN FOOD PURCHASE INTENTION DURING THE COVID-19 OUTBREAKIN INDONESIA (CASE OF GREATER JAKARTA) - David Hosanna Chianardi; Anggraeni Permatasari (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
In early 2020, the first case of CV19 was reported in Indonesia. Frozen food becomes a popular choice for someone who is looking for convenience and practical purpose during the pandemic. This paper aims to reveal the influence of perceived value, brand image, price fairness, product packaging, consumers’ lifestyle on frozen food purchase intention during CV19 in the Greater Jakarta area. This study used quantitative method with multiple regression analysis. An online questionnaire was distributed to respondents. The result from 154 respondents who have ever bought frozen food during CV19 was collected as the primary data. In the data collection process, the convenience and snowball sampling technique were utilized. For data analysis, the researcher used multiple regression analysis. The result shows that perceived value, product packaging, and consumers’ lifestyle significantly influence purchase intention towards frozen food during CV19. However, brand image and price fairness don’t influence purchase intention towards frozen food during CV19.Keywords: Purchase Intention, Perceived Value, Brand Image, Price Fairness, Product Packaging, Consumers’ Lifestyle, Covid-19 Pandemic.